1989
DOI: 10.1084/jem.169.3.625
|View full text |Cite
|
Sign up to set email alerts
|

Mixed isotype class II antigen expression. A novel class II molecule is expressed on a murine B cell lymphoma.

Abstract: The structures of Ia molecules expressed by two BALB/c B cell lymphoma lines, A20-1.11 (A20) and 2PK3, were analyzed in an effort to explain the differences in antigen-presenting capacity displayed by these cells. Alloreactive T cell hybridomas specific for I-Ad and antigen-specific, I-Ad-restricted T cells responded well to A20 as the APC. The same alloreactive T cell hybridomas responded weakly or not at all to 2PK3 and the responses of the antigen-specific, I-Ad-restricted T cells were consistently lower to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…In the special case of B cell malignancies, however, it is possible that the tumor can become its own APC, with increased expression of costimulatory molecules, enabling it to present its own Ags directly to T cells (9,42). A20 cells, an MHC class I-and class II-expressing B cell lymphoma, has long been recognized as a powerful APC (43,44). Indeed, we demonstrated that CpG enhances the expression of CD80 and CD86 on A20 lymphoma cells and it has been shown by others that CpG increases the costimulatory capacities of the A20 lymphoma cells (45,46).…”
Section: Discussionmentioning
confidence: 61%
“…In the special case of B cell malignancies, however, it is possible that the tumor can become its own APC, with increased expression of costimulatory molecules, enabling it to present its own Ags directly to T cells (9,42). A20 cells, an MHC class I-and class II-expressing B cell lymphoma, has long been recognized as a powerful APC (43,44). Indeed, we demonstrated that CpG enhances the expression of CD80 and CD86 on A20 lymphoma cells and it has been shown by others that CpG increases the costimulatory capacities of the A20 lymphoma cells (45,46).…”
Section: Discussionmentioning
confidence: 61%
“…Since Ea chain cannot be expressed on the membrane by itself, it must be pairing with the surface expression. The existence of an Ea + Aß hybrid molecule has recently been shown in a BALB/c lymphoma (20). We were not able to pick up this hybrid molecule by immunoprecipitation .…”
Section: Discussionmentioning
confidence: 76%
“…The frequency of stable B-cell/T-cell conjugates (>10 min lifetime) was also much higher with 2PK3 and correlated well with the strength of initial signals. The difference observed in the T-cell stimulating capacity of the two APCs is likely due to two major factors: (i) 2PK3 cells express I-E d and I-E d ␣ /I-A d ␤ mixed isomer forms of MHC-II at the same level as A20 cells express normal I-E d and I-A d forms in comparable extent [36]. This situation results in more potential recognition sites (and maybe higher stability of peptide-MHC complexes) on 2PK3 than on A20 cells for IP12-7 T-cells.…”
Section: Discussionmentioning
confidence: 95%